Topical corticosteroid allergy: Results of sequential testing to a corticosteroid series in New Zealand. (18th January 2021) - Murphy, Victoria L.; Patel, Denesh C.; Lamb, Steven R.; Cheng, Harriet S.
Abstract: Background: Our institution tests the European Baseline Series (EBS) and a steroid series sequentially in all patients presenting for patch testing. The rate of steroid sensitization in New Zealand has not previously been documented. Objectives: To investigate the rate of corticosteroid sensitization and assess additional benefit of testing the full steroid series over the steroid allergy markers in the EBS. Methods/Patients: Retrospective analysis of all patient demographics and patch test results over a 5‐year period (2014 to 2019) was performed at a tertiary patch test clinic in Auckland, New Zealand. Results: A total of 319 patients completed patch testing, and 4.4% were sensitized to one or more corticosteroids. As much as 79% of positive reactions were of current relevance; 11/14 reactions were to tixocortol pivalate or budesonide. The "number needed to test" to detect one additional case of corticosteroid sensitization by using the full corticosteroid series over the EBS alone was 107. Conclusions: Although corticosteroid sensitization was not uncommon in our population, the results suggest that sequential testing with the corticosteroid markers (budesonide and tixocortol) in the standard series alone is adequate. The additional corticosteroid series should be added if the markers are positive or where there is a clinical suspicion of corticosteroid allergy.